Characterization of key ingredients of essential oil-loaded biopolymer-based transdermal patches - Prasamsha Panta; Elina Maharjan; Holger Schönherr; Rameshwar Adhikari; Achyut Adhikari; Rajani Malla (Bibechana, 2025)
The study aimed to characterize the key ingredients used in developing transdermal patches made from biopolymers to deliver essential oils using Fourier Transmission Infrared (FTIR) spectroscopy, Scanning Electron Microscopy (SEM), Thermogravimetric Analysis (TGA), and rheological analysis. While FTIR spectroscopy and SEM were used to investigate the structural properties and intermolecular interaction within chitosan (CH), methylcellulose (MC), and carboxymethyl cellulose (CMC) as well as wintergreen essential (WG) oil), the TGA revealed the thermal degradation profiles of CH, MC, and CMC. Rheological analyses revealed that the polymer concentration and the solvent chosen significantly influenced the processability of the polymers. TGA analysis demonstrated that an initial decomposition of CH took place at 275 °C, while MC and CMC exhibited initial degradation around 260 °C. Based on the structural, rheological, and thermal properties, the suitability of the used biopolymer in combination with the WG oil for fabricating the transdermal patch was demonstrated.